Strategi Manajemen Pengembangan Usaha Mikro dan Kecil Olahan Pangan di Kabupaten Morowali Utara - M, Rudin; Bakarbessy, Maria Lea Frensy; Fadlun, Fadlun (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2024)
Abstract The purpose of this study is to determine and analyze the development of micro, small, and medium enterprises in food processing in North Morowali Regency. This type of research is qualitative, with four selected informants. Data collection uses observation, interview, and documentation techniques. The data analysis techniques used are (1) data collection, (2) data reduction, (3) data presentation, (4) verification, and (5) conclusion. The results of this study indicate that: (1) The development of Micro, Small, and Medium Enterprises (MSMEs) in food processing in North Morowali Regency has been going well. (2) There are several supporting factors in the development of MSMEs, namely: (a) government attention to MSME actors, which is manifested through cash assistance, provision of production equipment, and marketing facilities through social media and exhibitions organized by the government; (b) the existence of information technology facilities such as smartphones, Zoom applications, YouTube, Google, and print media, which greatly assist MSME actors in promoting their products. (3) On the other hand, there are several inhibiting factors in the development of MSMEs, including: (a) limited human resources who do not yet have competence in the MSME field; (b) limited business capital; (c) lack of promotional activities; and (d) difficulty in applying for business capital loans at banks.Keywords: Management, MSME and DevelopmentAbstrakTujuan penelitian ini adalah mengetahui dan menganalisis Pengembangan Usaha Mikro Kecil Olahan Pangan di Kabupaten Morowali Utara. Jenis Penelitian ini adalah penelitian kualitatif dengan informan yang dipilih sebanyak empat orang. Pengumpulan data menggunakan teknik pengamatan, wawancara dan dokumentasi. Teknik analisis data yang digunakan yaitu (1) Pengumpulan data (2) Reduksi Data (3) Penyajian Data (4) Verifikasi (5) Kesimpulan. Hasil penelitian ini menunjukkan bahwa: (1) Pengembangan Usaha Mikro Kecil (UMK) olahan pangan di Kabupaten Morowali Utara telah berjalan dengan baik. (2) Terdapat beberapa faktor pendukung dalam pengembangan UMK, yaitu: (a) perhatian pemerintah terhadap pelaku UMK, yang diwujudkan melalui bantuan tunai, penyediaan alat produksi, serta fasilitasi pemasaran melalui media sosial dan pameran-pameran yang diselenggarakan oleh pemerintah; (b) keberadaan fasilitas teknologi informasi seperti telepon pintar, aplikasi Zoom, YouTube, Google, dan media massa cetak yang sangat membantu pelaku UMK dalam mempromosikan produk mereka. (3) Di sisi lain, terdapat beberapa faktor penghambat pengembangan UMK, meliputi: (a) keterbatasan sumber daya manusia yang belum memiliki kompetensi di bidang UMK; (b) keterbatasan modal usaha; (c) kurangnya kegiatan promosi; dan (d) kesulitan pengajuan pinjaman modal usaha di perbankan.Kata Kunci: Manajemen, UMK dan Pengembangan